PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT ( TGT ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 013 BUKIT NENAS - Sipayung, Rasianna Sipayung Rasianna; Asyari, Mahmud Alpusari Mahmud; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is Classroom Action Research (CAR), which is done to improve the learning outcomes of fifth grade students of SDN 013 Bukit Nenas with implementing cooperative learning model Team Games Tournament (TGT). This research was conducted in April 2014 with 2 cycles executed. The subjects were 013 fifth grade students of SDN Bukit Nenas, amounting to 24 people which is used as the data source. Data collection instrument in this study is the observation activity sheets and teacher and student learning outcomes. Average - The average student learning outcomes before the 55.20 of 27 students who completed only 7 with classical completeness 26.00 % while students who did not complete 20 people with classical completeness 74.00 % .At this study are presented the percentage of teachers and student activities and the results of the first cycle and the daily test cycle activity II. Persentase teacher in cycle I and II was increased to 92.12 % 89.64 student activity in cycle I and II was 87.50, rising to 89.76 average - average learning outcomes students in the first cycle was 76.26 of 27 people, who completed 18 percent of people with a 75,00 % average .flat student learning outcomes is a 80,18 second cycle of the 27 people who completed 23 people with percentage of 81,00 %. It can be concluded that the hypothesis is that if the applied model types Cooperative Learning Teams Games Tournament (TGT), then can improve learning outcomes fifth grade students of SDN 013 Bukit Nenas acceptable. Keywords: Cooperative Learning Model Implementation Team Type Games Tournament, science learning outcomes.